Addie Model in Analyst Training to Improve the Professionality of Mawar Clinic Lab Officers in Bandung City - Feronica Melinda Muskitta; Rian Andriani; Bambang Sukajie (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the training model for Medical Laboratory Technology Analysts (ATLM) in improving staff professionalism at the Mawar Clinical Laboratory in Bandung City. The research employed a qualitative case study design with data collected through in-depth interviews, observations, and documentation reviews. Data analysis was conducted using the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation—supported by thematic coding assisted by NVivo software to enhance analytical rigor and validity. The findings indicate that the analysis phase identified the need to strengthen technical competencies, SOP comprehension, time management, and soft skills among ATLM staff. In the design phase, a competency-based training curriculum was developed according to laboratory standards. During the development phase, training modules, media, and evaluation instruments were produced and validated. Implementation was carried out through blended learning, hands-on practice, and direct supervision. The evaluation demonstrated improvements in ATLM professionalism, particularly in accuracy, discipline, SOP compliance, service quality, and work ethics. Overall, the ADDIE based training model proved relevant and effective in enhancing laboratory staff professionalism and is recommended for sustainable competency development within Mawar Clinical Laboratory.